ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN INDUSTRI PARIWISATA DAN REKREASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fernanda Intan Mustikaningrum (2022)
This study is a quantitative study with the aim of seeing whether there is an influence between leverage, profitability, and firm size on financial distress in a company. The population used in this study is the tourism and recreation industry companies with a total of 23 companies listed on the Indonesia Stock Exchange for the 2016-2020 period. To obtain a sample point, this study used a purposive sampling method so as to obtain a sample point of 23 companies. The hypothesis testing tool used is logistic regression analysis using E-views 10.0 software with a threshold value of 5% and also using Microsoft Excel 2013 as a data analysis tool. This study provides results, namely (a) leverage calculated using the Debt to Assets Ratio (DAR) proxy has an effect on financial distress, (b) profitability measured using the Return on Assets (ROA) proxy has no effect on financial distress, (c) company size calculated using the SIZE proxy has no effect on financial distress.